From Unitary Urbanism to the critique of urbanism: a tour across the concept of city and urban in the Situationist International movement - Gonçalves, Glauco Roberto (Programa de Pós-Graduação de Geografia Humana e Programa de Pós-Graduação de Geografia Física, 2017)
The Situationist International have had great dedication on the studies, practices and textual elaborations of important topics necessary to criticize and to radically transform life. In this sense the urban and the cities were highlighted within the Letterist’s and Situationist’s magazines’ debates. This text approaches the debates presented by these groups in the fields of urban and urbanistic conceptions; it also proposes a constitutive historical path to the way of understanding and action of these issues for the Letterist and Situationist movement. This article’s discussion will flow, as shown by the title of the text, from the proposition process of urban planning concepts – most notably those aimed at Unitary Urbanism – to the radical critique of urbanism.